In situ growth novel cubic copper hydroxyl phosphate and its utilization as a highly sensitive hydrogen peroxide amperometric sensor. (September 2020) - Kong, Quan; Li, Yanjie; Fan, Nanyu; Guan, Hongtao; Dong, Chengjun; Chen, Gang
Graphical abstract: Highlights: Cubic copper hydroxyl phosphate has been in situ grown for non-enzymatic H2 O2 detection. The Cux (PO4 )y (OH)z appears cubic shape with 100–200 nm in size. The pre-treatment of CF with HCl followed corrosion by urea phosphate plays a critical role. The Cux (PO4)y (OH)z /CF electrode shows a high sensitivity (7056 μA mM −1  cm −2 ) for H2 O2 . The outstanding performances are attributed to the high electrocatalytic activity. Abstract: It is of crucial importance to fabricate suitable sensing materials to sensitively detect hydrogen peroxide (H2 O2 ). Herein, cubic copper hydroxyl phosphate consisting two phases of Cu2 (PO4 )(OH) and Cu5 (PO4 )2 (OH)4 (abbreviated as Cux (PO4 )y (OH)z ) has been in situ grown for non-enzymatic H2 O2 detection using Cu foam (CF) as both precursor and support substrate. Controllable experiments indicate that the pre-treatment of CF with HCl followed corrosion by urea phosphate plays a critical role for the formation of cubic Cux (PO4 )y (OH)z . The Cux (PO4 )y (OH)z /CF electrode is employed as a H2 O2 amperometric sensor, resulting in a low limit of detection (0.1 u M), high sensitivity (7056 μA mM −1  cm −2 ) and fast response with excellent selectivity and stability. Apart from the promotion in electron and mass transfer by Cu foam substrate, the outstanding performances can be attributed to the high electrocatalytic activity of Cux (PO4 )y (OH)z including copper and phosphorus ions and the unique structure.